Analysis of Brain Lesion Impact on Balance and Gait Following Stroke - Handelzalts, Shirley; Melzer, Itshak; Soroker, Nachum (Frontiers in Human Neuroscience, 2019)
Falls are a leading cause of serious injury and restricted participation among persons with stroke (PwS). Reactive balance control is essential for fall prevention, however, only a few studies have explored the effects of lesion characteristics (location and extent) on balance control in PwS. We aimed to assess the impact of lesion characteristics on reactive and anticipatory balance capacity, gait, and hemiparetic lower limb function, in PwS. Forty-six subacute PwS were exposed to forward, backward, right and left unannounced horizontal surface translations in 6 increasing intensities, while standing. Fall threshold (i.e., perturbation intensity that results in a fall into the harness system) was measured. In addition, the Berg Balance Scale (BBS), 6 Minute Walk Test (6MWT) and Lower Extremity Fugl-Meyer (LEFM) were measured. Lesion effects were analyzed separately for left- and right-hemisphere damaged (LHD, RHD) patients, using voxel-based lesion-symptom mapping (VLSM). Our results show that voxel clusters where damage exerted a significant impact on balance, gait and lower-limb function were found in the corticospinal tract, in its passage in the corona radiata and in the posterior limb of the internal capsule. Additional significant impact was found to lesions affecting the putamen and the external capsule. Balance, gait, and hemiparetic lower limb function showed much overlap of the corresponding ‘significant’ voxel clusters. Test scores of RHD and LHD patients were affected largely by damage to homologous regions, with the LHD group showing a wider distribution of ‘significant’ voxels. The study corroborates and extends previous findings by demonstrating that balance control, gait, and lower limb function are all affected mainly by damage to essentially the same brain structures, namely - the corticospinal tract and adjacent structures in the capsular-putaminal region.